Do Neighborhood Demographics Modify Walking Group Intervention Effectiveness in Urban Neighborhoods?. Issue 1 (January 2017) - Schulz, Amy J.; Mentz, Graciela B.; Kwarteng, Jamila; Israel, Barbara A.; Gamboa, Cindy; Sand, Sharon L.; Gaines, Causandra; Reyes, Angela G.; Rowe, Zachary
Objectives . We assessed the effects of neighborhood composition on effectiveness of the Walk Your Heart to Health (WYHH) intervention in promoting physical activity and reducing cardiovascular risk (CVR) in low-to-moderate–income, predominantly non-Latino Black (NLB) and Latino communities. Method . Multilevel models assessed modifying effects of neighborhood composition on (1) WYHH adherence/participation at 8 weeks and 32 weeks, (2) associations between participation and steps, and (3) associations between steps and CVR. Results . Approximately 90% of participants were women. Neither neighborhood poverty nor racial composition modified intervention participation at 8 weeks. At 32 weeks, residents of high percentage–NLB neighborhoods that also had high poverty rates had reduced participation. Neighborhood composition did not modify associations between participation and steps or between steps and CVR. Neighborhood percentage poverty and NLB were positively associated with CVR. Conclusion . Positive associations between participation in the WYHH program and physical activity, and CVR did not differ by neighborhood composition. Efforts to address challenges to long-term participation are warranted for residents of racially segregated, high-poverty neighborhoods. Residents of racially segregated neighborhoods with high concentrations of poverty experience disproportionately high risk for cardiovascular disease and can benefit from interventions such as WYHH that increase physical activity and reduce CVR.